The lexicographic project «The 250 idioms and expressions: principles of formation» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article describes the history of  N.V. Gogol’s idioms and expressions in Russian and Ukrainian eptography. The theoretical and practical principles of it’s formation of dictionary are mentioned in «The 250 idioms and expressions of N. V. Gogol (The Russian-Ukrainian explanatory dictionary). The 250 idioms and expressions of N. V. Gogol (The Ukrainian-Russian explanatory dictionary)».
Keywords: idiom an expression; eptography; quotation; dictionary